Russian Foreign Policy in Transition: Concepts and Realities - Melville, Andrew (Amsterdam University Press, 2005)
Divided into three parts, the book presents official translated documents in the first section that outline, among other things, the formation of the Commonwealth of Independent States (CIS), the military doctrine of the Russian Federation, and the agreement on security and cooperation between NATO and Russia. These documents are an essential first step in understanding the shape and context of Russian foreign policy from the demise of the Soviet Union up to the present.